A randomised trial comparing endometrial resection and abdominal hysterectomy for the treatment of menorrhagia. Issue 6814 (30th November 1991) - Gannon, M J; Holt, E M; Fairbank, J; Fitzgerald, M; Milne, M A; Crystal, A M; Greenhalf, J O
Abstract : OBJECTIVE--To determine the advantages and disadvantages of endometrial resection and abdominal hysterectomy for the surgical treatment of women with menorrhagia. DESIGN--Randomised study of two treatment groups with a minimum follow up of nine months. SETTING--Royal Berkshire Hospital, Reading. SUBJECTS--51 of 78 menorrhagic women without pelvic pathology who were on the waiting list for abdominal hysterectomy. TREATMENT--Endometrial resection or abdominal hysterectomy (according to randomisation). Endometrial resections were performed by an experienced hysteroscopic surgeon; hysterectomies were performed by two other gynaecological surgeons. MAIN OUTCOME MEASURES--Length of operating time, hospitalisation, recovery; cost of surgery; short term results of endometrial resection. RESULTS--Operating time was shorter for endometrial resection (median 30 (range 20-47) minutes) than for hysterectomy (50 (39-74) minutes). The hospital stay for endometrial resection (median 1 (range 1-3) days) was less than for hysterectomy (7 (5-12) days). Recovery after endometrial resection (median 16 (range 5-62) days) was shorter than after hysterectomy (58 (11-125) days). The cost was 407 pounds for endometrial resection and 1270 pounds for abdominal hysterectomy. Four women (16%) who did not have an acceptable improvement in symptoms after endometrial resection had repeat resections. No woman has required hysterectomy during a mean follow up of one year. CONCLUSION--For women with menorrhagia who have no pelvic pathology endometrial resection is a useful alternative to abdominal hysterectomy, with many short term benefits. Larger numbers and a longer follow up are needed to estimate the incidence of complications and the long term efficacy of endometrial resection.